Peering into the Dark Side: Magnesium Lines Establish a Massive Neutron Star in PSR J2215+5135 (2018)
New millisecond pulsars (MSPs) in compact binaries provide a good opportunity to search for the most massive neutron stars. Their main-sequence companion stars are often strongly irradiated by the pulsar, displacing the effective center of light from their barycenter and making mass measurements uncertain. We present a series of optical spectroscopic and photometric observations of PSR J2215+5135, a “redback” binary MSP in a 4.14 hr orbit, and measure a drastic temperature contrast between the dark/cold (TN = 5660- + 380 260 K) and bright/hot (TD = 8080- + 280 470 K) sides of the companion star. We find that the radial velocities depend systematically on the atmospheric absorption lines used to measure them. Namely, the semi-amplitude of the radial velocity curve (RVC) of J2215 measured with magnesium triplet lines is systematically higher than that measured with hydrogen Balmer lines, by 10%. We interpret this as a consequence of strong irradiation, whereby metallic lines dominate the dark side of the companion (which moves faster) and Balmer lines trace its bright (slower) side. Further, using a physical model of an irradiated star to fit simultaneously the two-species RVCs and the three-band light curves, we find a center-of-mass velocity of K2 = 412.3 ± 5.0 km s?1 and an orbital inclination i = 63°.9- + 2.7 2.4. Our model is able to reproduce the observed fluxes and velocities without invoking irradiation by an extended source. We measure masses of M1 = 2.27- + 0.15 0.17 Me and M2 = 0.33- + 0.02 0.03 Me for the neutron star and the companion star, respectively. If confirmed, such a massive pulsar would rule out some of the proposed equations of state for the neutron star interior.